De elbeszélhető…: (Borbély Szilárd „Nyugszol a’ nyárfáknak lengő hívesében”. Tanulmányok Csokonairól című könyvéről) - Lakner, Lajos (Studia Litteraria, 2024)
In Szilárd Borbély’s book, life and literature are almost inextricably linked. In order to separate them, the first part of this essay presents – or rather describes – the book chapter by chapter, and then explores what might have shaped and determined the author’s focus and methodology. In particular, the paper examines why the book focuses on the question of life’s transcribability into text and the interplay between reality and fiction, as not only Csokonai’s life story, but also that of Szilárd Borbély, compel us to examine the strategies they used to textualize their lives and make them narrative.